Adaptation and Maladaptation of the Heart in Obesity - Harmancey, Romain (2008)
Obesity affects the cardiovascular system at many different levels, including the heart muscle itself. Clinical and experimental studies have shown an accumulation of triglycerides and other lipid species in cardiomyocytes. Analogous to hepatic steatosis, investigators have introduced the term “cardiac steatosis”. The present review addresses the complex relationships between cardiac fuel homeostasis, insulin resistance, and proposed mechanisms of damage to cardiomyocytes in different models of obesity, insulin resistance, and lipotoxicity. Specifically, the review weighs the evidence whether there is a heart muscle disorder in human obesity. It discusses how adipokines can modulate cardiac metabolism, and it focuses on the metabolic remodeling accompanying increased fatty acid supply in the heart of rodent models of lipotoxicity, with special attention to the role played by mitochondrial uncoupling and futile cycling. We stress the notion that, in spite of the many proposed mechanisms, cardiac lipotoxicity is still a hypothesis rather than an established pathophysiologic principle. Although the concept of a “lipotoxic cardiomyopathy” seems attractive, we propose instead a series of steps on a path from adaptation to maladaptation of the heart in obesity. A case in point is insulin resistance of the heart which may be both adaptive (protecting the heart from excess fuel) or maladaptive (associated with reactive oxygen species formation and activation of signaling pathways of programmed cell death). The present literature reflects an extraordinary complexity of the heart’s metabolic, functional and structural changes in obesity.